Viajes con viático y sin viático - Prado Biezma, Javier del (Revista de Filología Románica, 2006)
Starting from the concept of life as a journey, and of writing as a journey, as well as from some reflections about the etymology of the word, this work proposes the different types of journeys with viaticum, such as pilgrimages, cultural journeys or discoveries or colonization, and the idea of journey without viaticum as a metaphor of modern man.